Tinjauan Sosiologi Hukum terhadap Permohonan Dispensasi Kawin sebagai Sarana Kepastian Hukum dan Kepentingan Terbaik bagi Pelaku Pernikahan Usia Dini - Hardiansyah, Faisal; Febrianti, Yenny; mahipal, Mahipal (Advances In Social Humanities Research, 2024)
This paper examines the process of examining marriage dispensation cases prior to and following the enactment of Supreme Court Regulation Number 5 of 2019 concerning Guidelines for Adjudicating Marriage Dispensation Cases. This paper was written using a qualitative research method, specifically normative and empirical juridical approaches. According to the findings of this study, the provisions of Supreme Court Regulation Number 5 of 2019 have explicitly regulated several things that are not specifically regulated in the formal and material rules governing marriage dispensation. The adoption of this regulation is an anticipation and standardization for judges in making legal decisions, so that court decisions pay more attention to the best interests of children when granting a marriage dispensation application.